Radio frequency and microwave power amplifiers Volume 2 - Grebennikov, Andrei, 1956- (Institution of Engineering and Technology, 2019)
This book deals with the following topics: High-efficiency power amplifier design; High-efficiency Doherty power amplifiers; Envelope tracking techniques; Outphasing power amplifiers; Combiner synthesis for active load-modulation-based power amplifiers; Power amplifier design based on nonlinear embedding models with design examples; CMOS power amplifiers; Behavioral modeling and linearization; Multiband/multichannel power amplifier linearization; and Distributed power amplifiers
Keywords: Power amplifiers.; elektronické knihy; electronic books